Study of instability driving inward particle flux during the formation of transport barriers at the edge of the HL-2A tokamak. (11th November 2016) - Kong, D.F.; Lan, T.; Liu, A.D.; Yu, C.X.; Zhao, H.L.; Shen, H.G.; Yan, L.W.; Dong, J.Q.; Xu, M.; Zhao, K.J.; Cheng, J.; Duan, X.R.; et al.
Abstract: An electrostatic coherent mode with a frequency of 20 ∼ 100 kHz can be observed during the formation of transport barriers in high-confinement-mode plasma in the HL-2A tokamak, using reciprocating Langmuir probes. The mode drives a strong inward particle flux measured directly with four-tip probes with values comparable to the particle flux at the striking point in the divertor, which has also been validated by the measurement of other diagnostics. Several characteristics simultaneously indicate that the mode is an ion mode excited at the edge, which plays an important role in the formation of transport barriers besides particle diffusion.